How strong is the case for dollarization in Central America? An empirical analysis of business cycles, credit market imperfections and the exchange rate - Nannette Lindenberg; Frank Westermann (Osnabrück University, Institute of Empirical Economic Research, 2010)
In this paper, we contrast two different views in the debate on official dollarization. The Mundell (1961) framework of optimal currency areas and a model on boom-bust cycles, by Schneider and Tornell (2004), who take account of credit market imperfections prevalent in middle income countries. We highlight that the role of the exchange rate is strikingly different in the two models. While in the Mundell framework the exchange rate is expected to smooth the business cycle, the other model predicts that the exchange rate plays an amplifying role. We empirically evaluate both models for eight highly dollarized Central American economies, and find that the main benefit of official dollarization derives from avoiding a mismatch between foreign currency liabilities and domestic revenues, as well as the boom-bust episodes that are likely to follow from it. Using a new method of Cubadda (1999, 2007), we furthermore test for cyclical comovement and reject the hypothesis that the countries form an optimal currency area with the United States according to the Mundell definition.
Keywords: E32; E52; F36; O54; 330; dollarization; real exchange rate; business cycle comovement; serial correlation common feature; boom-bust cycles; credit market imperfections; Central America